DIGITAL HEALTH AND SELF-CARE IN PEOPLE WITH INTESTINAL OSTOMIES: AN INTEGRATIVE REVIEW (Estima – Brazilian Journal of Enterostomal Therapy, 2021)
Objective: synthesize the scientific production related to digital health in ostomies to promote self-care. Method:integrative review with research in online databases, seeking to answer the following guiding question: What are the digital approaches used to teach self-care to patients with ostomy identified in the publications? Results: six different ways of using digital health to promote self-care in people living with intestinal ostomies were identified. Five were published in the National Library of Medicine (MEDLINE) database and one published in the databases Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS) and Base de Dados de Enfermagem daBiblioteca Virtual em Saúde (BDENF),in the period from 2017 to 2020. Conclusion: the six approaches studied can be used simultaneously in individuals with ostomies and can be considered complementary, as they act in different aspects of the individual’s routine, with the ultimate goal being to improve the quality of life of theperson with an intestinal ostomy.